Chaperonin-Containing TCP1 Subunit 5 Protects Against the Effect of Mer Receptor Tyrosine Kinase Knockdown in Retinal Pigment Epithelial Cells by Interacting With Filamentous Actin and Activating the LIM-Kinase 1/Cofilin Pathway - Feng, Lujia; Li, Haichun; Du, Yong; Zhang, Ting; Zhu, Yingting; Li, Zhidong; Zhao, Ling; Wang, Xing; Wang, Gongpei; Zhou, Linbin; Jiang, Zhaorong; Liu, Zheng; et al. (Frontiers in Medicine, 2022)
Retinitis pigmentosa (RP), characterized by the gradual loss of rod and cone photoreceptors that eventually leads to blindness, is the most common inherited retinal disorder, affecting more than 2.5 million people worldwide. However, the underlying pathogenesis of RP remains unclear and there is no effective cure for RP. Mutations in the Mer receptor tyrosine kinase (MERTK) gene induce the phagocytic dysfunction of retinal pigment epithelium (RPE) cells, leading to RP. Studies have indicated that filamentous actin (F-actin)—which is regulated by chaperonin-containing TCP1 subunit 5 (CCT5)—plays a vital role in phagocytosis in RPE cells. However, whether CCT5/F-actin signaling is involved in MERTK-associated RP remains largely unknown. In the present study, we specifically knocked down MERTK and CCT5 through siRNA transfection and examined the expression of CCT5 and F-actin in human primary RPE (HsRPE) cells. We found that MERTK downregulation inhibited cell proliferation, migration, and phagocytic function; significantly decreased the expression of F-actin; and disrupted the regular arrangement of F-actin. Importantly, our findings firstly indicate that CCT5 interacts with F-actin and is inhibited by MERTK siRNA in HsRPE cells. Upregulating CCT5 using CCT5-specific lentiviral vectors (CCT5-Le) rescued the cell proliferation, migration, and phagocytic function of HsRPE cells under the MERTK knockdown condition by increasing the expression of F-actin and restoring its regular arrangement via the LIMK1/cofilin, but not the SSH1/cofilin, pathway. In conclusion, CCT5 protects against the effect of MERTK knockdown in HsRPE cells and demonstrates the potential for effective treatment of MERTK-associated RP.